Moving Toward Telehealth Surveillance Services for Toddlers at Risk for Autism During the COVID-19 Pandemic - Conti, Eugenia; Chericoni, Natasha; Costanzo, Valeria; Lasala, Roberta; Mancini, Alice; Prosperi, Margherita; Tancredi, Raffaella; Muratori, Filippo; Calderoni, Sara; Apicella, Fabio (Frontiers in Psychiatry, 2020)
Since 2016, the project ‘Early Bird Diagnostic Protocol for Autism Spectrum Disorders (ASD)’ funded by the Italian Ministry of Health has been operative at IRCCS Fondazione Stella Maris (FSM), Pisa (IT), with the main aim to develop early age-specific diagnostic protocols by longitudinally enrolling two different populations at risk for ASD: (i) toddlers with older siblings with ASD (FR), who are vulnerable to ASD; (ii) clinically-referred toddlers (CR) for suspected ASD by a child psychiatrist or pediatrician. On January 30, 2020, when the World Health Organization declared the outbreak of coronavirus disease 2019 (COVID-19), 136 patients (85 FR; 51 CR; 93 males; 43 females;) had been enrolled in the project with 324 completed time points and 64 still missing. Considering both the huge psychological burden on families with toddlers at risk for ASD during lockdown and the longitudinal studies reporting the positive “surveillance effect” in terms of better outcome in at risk toddlers, our priority has been to maintain regular contact and support to enrolled families. To do this, the research team, being authorized for smart-working research activities, has set-up a detailed, as more comparable as possibile, remote surveillance protocol (RSP). The RSP includes three online interviews and one online video-registration of parent-child play. In the current community case study the authors report the telepsychiatry procedure and discuss possible future directions in developing remote assessment and new evaluation modalities of echological parent-child play video recordings in at risk population. Hopefully, the surveillance protocol has the final aim to detect risk and activate early tailored intervention.